PEMANFAATAN SARANA DAN PRASARANA BIMBINGAN DAN KONSELING DI SMP NEGERI SE-KECAMATAN LENGAYANG KABUPATEN PESISIR SELATAN - Zulbaida, Zulbaida; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research was motivated by utilization of facilities and infrastructure guidance and counseling are not effective by counselor at school. This study aimed to look at how utilize of facilities and infrastructure were done by counselor to make effective service activities at SMP Negeri se-Kecamatan Lengayang Kabupaten Pesisir Selatan. The research objectives are: 1) Describe the form of utilization of  facilities guidance and counseling by counselor at SMP Negeri se-Kecamatan Lengayang Kabupaten Pesisir Selatan, 2) Describe form of infrastructure utilization by counselor at SMP Negeri se-Kecamatan Lengayang Kabupaten Pesisir Selatan. This research was qualitative research. This research took six existing counselor at SMP Negeri  se-Kecamatan Lengayang Kabupaten Pesisir Selatan, as research informants they were: SMP N 1, 2, 3 and 4 Lengayang. Data were collected through interviews and observation and documentation of the utilization of counseling and guidance facilities and infrastructure  by counselor. From the analysis of interviews and observations revealed that counselor difficulty carrying out activities with utilization guidance and counseling  facilities and infrastructure. The existing facilities: data collection tool, tool storage, administrative supplies and complete support  was not complete  while infrastructure that provide there like: workspace counselor, living and individual counseling.